Agent-Oriented Modelling for Blockchain Application Development: Feasibility Study - LiBin, Michelle Ten; WaiShiang, Cheah; Khairuddin, Muhammad Asyraf B; Mit, Edwin; Erianda, Aldo (Society of Visual Informatics, 2021)
Blockchain application development has received much attention nowadays. As development is complex and challenging, a systematic approach is needed to improve the product, services, and process quality. Despite the introduction of techniques, there are still inadequate models for demonstrating the blockchain's internal architecture. Hence, there is a gap when developing the blockchain application, a gap in the modelling environment of a blockchain development application. This paper introduces a new insight into blockchain application development through Agent-Oriented Modelling (AOM). AOM is a methodology for complex socio-technical system development, and we believe that it can reduce the complexity of implementing the blockchain application. In this paper, the AOM is used to model a blockchain-based